Genomics and bioinformatics enabled insights into lifestyle and aquatic adaptation of a food borne pathogen, Vibrio parahaemolyticus / Suma Tiruvayipati - Suma , Tiruvayipati (2015)
The onset of Next-generation sequencing (NGS) invoked the development of a large number of quality control (QC), assembly, annotation, and alignment tools. Bacterial genome data when processed with NGS tools have individual outputs. This effects further analysis and research related to host-pathogen studies. A defined set of bacterial genomes along with Vibrio parahaemolyticus PCV08-7 (VPPCV08-7) (an important bacterial isolate from prawn (Macrobrachium rosenbergii) in the current thesis) were selected for further bioinformatic analysis and experimentation. Strategies of High quality filtering, Trimming, Adaptor filtering and N’s removal based on which seven different pipelines (Pipeline 1, 2, 3, 4, 5, 6 & Trim-Adaptor-Highquality (TAH) pipeline) made, were used. Pre-existing QC tools have been utilized in the current study. The TAH pipeline had been used on VPPCV08-7 genome data to complete the draft genome constituting of two chromosomes. The genome adaptation of Vibrio parahaemolyticus strains to prawn could lead to host requisition towards pathogenic infections which can be further understood by gleaning into the organization of pathogenicity islands, virulence genes and the evolution of house-keeping genes among the different strains of the bacteria. V. parahaemolyticus phylogeny with gbpA in comparison to the 16S rRNA gene as well as the house-keeping dnaB, deaD genes has been done. The interesting factor of gbpA (N-acetylglucosamine-binding protein A) gene, of its interaction with the epithelial chitin surfaces was observed in the present study in response to magnesium sulphate (MgSO4.7H2O) environment in the presence of carapace and commercial chitin flakes. Our results showed the importance of the QC strategy “Trimming” with a cut-off value ≥30 phred score, applying it as the first QC tool followed by adaptor and high quality filtering could help use maximum percentage of raw read data. On application to different NGS data of VPPCV08-7 showed a good percentage of usage of read data. This helped analyse the draft genome which adds to an important gastro-intestinal pathogen repertoire. Followed by the phylogenetic relations between the 52 different V. parahaemolyticus strains with 16S rRNA, deaD, dnaB and gbpA which portray how randomly phylogenetic branches are formed. This showed selecting a house-keeping gene to relate to the evolutionary past of any strain specific to a country or location could play a major role in phylogeny. Lastly, our in vitro experiment and RT-PCR findings showed an increase in expression of gbpA in the presence of magnesium compound while significantly lower expression on addition with chitin and carapace. This explains that during the “molting” of prawn the gbpA expression could increase, therefore increasing the chances of bacterial interactions with the host epithelial chitin. Our study supports the use of phred quality ≥30, QC’s significance in dealing with sequencing data and how the roles of host-pathogenenvironment together need to be dealt to elucidate any further possibility of entry of the pathogen into the host. The data could give insights to the scientific community about precautious handling of NGS data for precision towards host-pathogen-environment studies.